Estudio Avifaunístico en la Hacienda Huerta Sacha de la Parroquia El Chaupi del cantón Mejía Provincia de Pichincha. - Tapia Chacón, Verónica Maribel (2019)
The present project is focused in perform an avifaunistica by means the application of technologies and instruments in the garden Sacha, of Chaupi parish, Mejía canton, Pichincha province. To announce the variety of birds that exists in the farm in spite of the avifaunistica wealth that it possesses, The Chaupi still is not recognized as a destination in the aviturismo. The situational diagnosis decided the geographical position, physical characteristics and the type of vegetation, they are determinant elements that allow the presence of different species. The field visits allowed to determine three zones of reference; that form part of the zoning of the area of study. The direct observation, transectos and counting of points was obtained as a result a record of 26 species of birds, 5 orders and 13 families; predominating over the order Passeriformes 70 %, Apodiformes 15 %, Falconiformes 7 %, Colombiformes and Charadiformes with a 4 %. The same ones that were identified and used for the elaboration of the field guide. With the obtained information a guide of birds was elaborated where information was included as order, family, common name, name in English, scientific name, reference, accompanied of photographies and description that show clearly to the species. Through this guide of birds, the user has in his hands an extensive knowledge of the presence of these species and will enjoy of the possibility of crossing paths that have been identified for the sighting of birds.